In Vivo Clearance Of Prostacyclin In Rabbits - Skrinska, V; Lucas, F; Chisolm, G; Thomas, G (Thrombosis and Haemostasis, 1981)
In vivo studies of prostacyclin (PGI2), a potent inhibitor of platelet aggregation, have been limited by its instability during isolation. A method has been developed in which PGI2 can be extracted from whole blood with negligible hydrolysis to 6-keto prostaglandin Fia (6-K-F1α) during collection and analysis. Bolus injections of 3H-PGI2 in ice cold saline were made through a cannula in the marginal ear vein of conscious male New Zealand white rabbits. Blood samples were drawn through the cannula at timed intervals into tubes containing Na2C03, 10 mg/ml. The PGI2 and 6-K-F1α were extracted from the plasma by passing an aliquot directly through an octadecylsilane reverse phase column. The prostaglandins were eluted with a boric acid-acetonitrile solvent system. The PGI2 and 6-K-F1α were then separated by high pressure liquid chromatography and samples of the injectate and blood were counted for radioactivity. Roughly half of the total radioactivity was collected from the bladder at termination, twenty minutes after the injection. Greater than 90% of the labeled PGI2 was cleared from the circulation in five minutes. The ratio of PGl2:6-K-F1α decreased faster in the blood in vivo than in an j[n vitro incubation of whole blood. This indicates a slower distribution or elimination of 6-K-F1α from the blood compartment and/or a more rapid distribution or metabolism of PGI2 in vivo.